MEDICINAL PLANTS USED TO TREAT CATTLE DISEASES IN NETRAKONA DISTRICT, BANGLADESH - Harun-or-Rashid, Md.; Tanzin, R.; Jahan, R.; Rahmatullah, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Most of the rural population of Bangladesh owns one or two cows or goats, which are used either for agricultural purposes (cows) or for selling to generate extra income (goats). For treatment of cattle diseases, they rely on traditional veterinary medicinal practitioners, who use medicinal plants to treat cattle ailments. We conducted an ethnomedicinal survey amongst the traditional veterinary medicinal practitioners in Netrakona district, Bangladesh to identify plants and cattle ailments for which the plants are used. Information on plants were obtained from the traditional cattle healers and individual specimens identified at the Bangladesh National Herbarium. A total of 46 plants distributed into 33 families were identified. The families included Acanthaceae, Alliaceae, Amaryllidaceae, Anacardiaceae, Araceae, Bromeliaceae, Cannabaceae, Convolvulaceae, Cyperaceae, Euphorbiaceae, Fabaceae, Gentianaceae, Lamiaceae, Leguminosae, Menispermaceae, Moraceae, Musaceae, Myrtaceae, Olaceae, Palmae, Piperaceae, Poaceae, Ranunculaceae, Rhamnaceae, Rubiaceae, Rutaceae, Solanaceae, Ulmaceae, Umbelliferae, Urticaceae, Verbenaceae and Zingiberaceae families. Of the families, the highest number of plants (three plants each) belonged to the Anacardiaceae, Euphorbiaceae, Myrtaceae, and Piperaceae families. The various cattle diseases that were claimed to be cured by the medicinal plants included fever, rigor, leg fractures, wound infections, diarrhea, meningitis, helminthiasis, common cold, enlargement of liver, body ache, asthma, retention of urine, mumps, piles, cataract, loss of hair, glossitis, and lack of milk production.